2021
DOI: 10.3390/app112110205
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Zingiber montanum and Their Pharmacological Activities with Focus on Zerumbone

Abstract: The genus Zingiber consists of about 85 species and many of these species are used as food, spices, and medicines. One of the species, Zingiber montanum (J. Koenig) Link ex A. Dietr. is native to Southeast Asia and has been extensively used as traditional medicines and food. The aim of this review was to collect and critically analyze the scientific information about the bioactive compounds and pharmacological activities of Z. montanum with focus on one of the main components, zerumbone (ZER). Various studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 152 publications
(129 reference statements)
0
9
0
1
Order By: Relevance
“…1 The rhizomes of this plant are extensively used as spice and as a crude drug in traditional medicine for the treatment of various conditions, such as inflammation, sprains, rheumatism, muscular pain, wounds, asthma, constipation, dyspepsia, gastritis, stomach bloating, and stomachache. [2][3][4][5][6] The extracts of Z. cassumunar contain many constituents, including phenylbutanoids, curcuminoids, flavonoids, terpenes, and quinones, and exhibit diverse bioactivities, including antioxidant, anti-inflammatory, anticancer, antihistaminic, and antimicrobial activities. [2][3][4][5] The main constituents isolated from rhizome extracts are phenylbutanoids (Figure 1), [7][8][9][10][11][12] such as (E)-1-(3 0 ,4 0 -dimethoxyphenyl)butadiene (DMPBD) (1), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-ol (2), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-yl acetate (3), and the dimers (±)-cis-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0 -dimethoxystyryl]-cyclohex-1-ene ( 4) and (±)-trans-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0dimethoxystyryl]-cyclohex-1-ene (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The rhizomes of this plant are extensively used as spice and as a crude drug in traditional medicine for the treatment of various conditions, such as inflammation, sprains, rheumatism, muscular pain, wounds, asthma, constipation, dyspepsia, gastritis, stomach bloating, and stomachache. [2][3][4][5][6] The extracts of Z. cassumunar contain many constituents, including phenylbutanoids, curcuminoids, flavonoids, terpenes, and quinones, and exhibit diverse bioactivities, including antioxidant, anti-inflammatory, anticancer, antihistaminic, and antimicrobial activities. [2][3][4][5] The main constituents isolated from rhizome extracts are phenylbutanoids (Figure 1), [7][8][9][10][11][12] such as (E)-1-(3 0 ,4 0 -dimethoxyphenyl)butadiene (DMPBD) (1), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-ol (2), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-yl acetate (3), and the dimers (±)-cis-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0 -dimethoxystyryl]-cyclohex-1-ene ( 4) and (±)-trans-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0dimethoxystyryl]-cyclohex-1-ene (5).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The extracts of Z. cassumunar contain many constituents, including phenylbutanoids, curcuminoids, flavonoids, terpenes, and quinones, and exhibit diverse bioactivities, including antioxidant, anti-inflammatory, anticancer, antihistaminic, and antimicrobial activities. [2][3][4][5] The main constituents isolated from rhizome extracts are phenylbutanoids (Figure 1), [7][8][9][10][11][12] such as (E)-1-(3 0 ,4 0 -dimethoxyphenyl)butadiene (DMPBD) (1), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-ol (2), (E)-4-(3 0 ,4 0 -dimethoxyphenyl)but-3-en-1-yl acetate (3), and the dimers (±)-cis-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0 -dimethoxystyryl]-cyclohex-1-ene ( 4) and (±)-trans-3-(3 0 ,4 0 -dimethoxy-phenyl)-4-[(E)-3 0 ,4 0dimethoxystyryl]-cyclohex-1-ene (5). Among these, DMPBD (1) has been identified as a potent active compound with antiinflammatory [11][12][13][14][15][16][17][18] and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural compounds such as berberine, curcumin, and zerumbone share the same features of low water solubility, poor bioavailability, and low cellular uptake, thereby limiting its clinical use for a wider range of diseases [42,79]. However, with the utilization of the nanotechnology approach, it is possible to improve their physiochemical characteristics, and formulating nanoparticles could enhance their therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The sesquiterpenoid zerumbone has also been detected in the essential oil of the rhizome of Z. montanum (J. Koenig) Link ex A. Dietr., where it constitutes one of the main components with relevant pharmacological activities (anticancer, anti-inflammatory, antioxidant, antimicrobial, gastric and liver protection) [ 55 ]. These results differ from those of other authors who reported a different chemical composition of the essential oil Z. montanum .…”
Section: Natural Sources Of Zerumbonementioning
confidence: 99%